Petroleum transportation handbook - Bell, Harold Sill (New York : McGraw-Hill, 1963)
This handbook reports the huge flow of petroleum commodities moving in daily commerce and the technology that has been developed to facilitate the movement make transportation as important branch of the petroleum industry.
Includes index
asm: 21/01/19
Loans
Keywords: Petroleum; Petroleum pipelines